Self-Injury Groups on Facebook - Niwa, Kendra D.; Mandrusiak, Michael N. (Canadian Journal of Counselling and Psychotherapy, 2012)
The present study examines the interactions within 4 Facebook groups devoted to supporting people who self-injure. Content analysis was used to analyze posts made to the group during the 3-month period of the study to explore the nature of interactions and the frequency of themes. High prevalence themes included responses to verbal abuse against those who self-injure (16.8%), the discussion of personal issues without directly requesting support (11.2%), and offers of direct support to other group members (11.0%). Notable phenomena and implications for treatment are discussed.